2009
DOI: 10.1111/j.1475-6773.2009.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

How Much Choice Is Too Much? The Case of the Medicare Prescription Drug Benefit

Abstract: Objective. To study the impact of the number of choices and age on measures of performance in choosing a Medicare prescription drug plan. Data Source/Study Setting. One hundred ninty-two healthy individuals age 18 and older, half age 65 or older, in Claremont, California. Study Design. Participants were randomly assigned to 3, 10, or 20 hypothetical drug plans and asked four factual questions. Statistical models controlled for experimental group, age, gender, race, education, income, marital status, and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 6 publications
8
95
0
Order By: Relevance
“…Few people are picking the most cost-effective plans: those that minimize the sum of premium payments and out-of-pocket copayments (20). Gruber (19) estimates that fewer than 10% of enrollees are choosing the cheapest plan; similar results were obtained in a different study by Heiss and colleagues (21).…”
Section: Wwwannualreviewsorg • Behavioral Economics Of Healthsupporting
confidence: 69%
“…Few people are picking the most cost-effective plans: those that minimize the sum of premium payments and out-of-pocket copayments (20). Gruber (19) estimates that fewer than 10% of enrollees are choosing the cheapest plan; similar results were obtained in a different study by Heiss and colleagues (21).…”
Section: Wwwannualreviewsorg • Behavioral Economics Of Healthsupporting
confidence: 69%
“…One investigation (Bundorf & Szrek, 2010) has shown that increasing the number of drug plans available (2, 5, 10, and 16) boosted participants' satisfaction with their choice; however, it also amplified their desire to see fewer options on the menu. Another study (Hanoch, Rice, Cummings, & Wood, 2009) found that larger drug plan choice-set size (10 and 20 compared to 3) reduced both older and younger participants' performance. It is perhaps not surprising, then, that earlier surveys found that the majority of older adults thought the Medicare Part D program was too complicated (Kaiser Family Foundation, 2006) and had too many choices ).…”
Section: Too Much Choice and Medicare Part Dmentioning
confidence: 99%
“…Regardless of the driving factor, Medicare beneficiaries would benefit from a simplified program and fewer number of plans (Cummings, Rice & Hanoch, 2009). Additionally, despite our efforts to provide a decision task that mimics the actual Medicare drug benefit, it was not possible to render them identical.…”
Section: Discussionmentioning
confidence: 99%
“…The instruments and design of the present study are based on an earlier investigation (Hanoch et al, 2009). A member of the research team briefly described the study and distributed surveys, the completion of which required approximately 10 minutes.…”
Section: Procedures and Materialsmentioning
confidence: 99%
See 1 more Smart Citation